2006
DOI: 10.1300/j050v16n01_05
|View full text |Cite
|
Sign up to set email alerts
|

Building a University Brand from Within: A Comparison of Coaches' Perspectives of Internal Branding

Abstract: Branding efforts have typically focused on external promotional strategies to develop brand image. Recently, the brand messages conveyed to employees of an organization have been recognized as being equally as important as the brand messages sent to external stakeholders. This study investigates the internal communication of the university brand with college coaches as the internal recipients, as well as external senders. In order to assess institutional internal branding efforts, college coaches who regularly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
85
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(91 citation statements)
references
References 24 publications
3
85
1
2
Order By: Relevance
“…It is generally concluded that the more internal branding is applied by management, the higher the likelihood that their employees' behavior will support the brand (e.g., Burmann & Zeplin, 2005;Judson et al, 2006;Vallaster & de Chernatony, 2005. In line with a study conducted by Judson et al (2006), internal branding activities are likely to assist an employee to have a clear understanding of her/his respective university's brand values and use these brand values in her/his everyday work. However, there are several terms which were used to refer to employees' behavior as an outcome of internal branding.…”
Section: Effects Of Internal Brandingmentioning
confidence: 68%
See 4 more Smart Citations
“…It is generally concluded that the more internal branding is applied by management, the higher the likelihood that their employees' behavior will support the brand (e.g., Burmann & Zeplin, 2005;Judson et al, 2006;Vallaster & de Chernatony, 2005. In line with a study conducted by Judson et al (2006), internal branding activities are likely to assist an employee to have a clear understanding of her/his respective university's brand values and use these brand values in her/his everyday work. However, there are several terms which were used to refer to employees' behavior as an outcome of internal branding.…”
Section: Effects Of Internal Brandingmentioning
confidence: 68%
“…Although the concept of internal branding in higher education institutions is recognized in the literature as a new phenomenon (Whisman, 2009), Judson et al (2006 found that when internal branding activities are implemented, employees are better able to reflect the brand values in their day-to-day operations.…”
Section: Internal Branding In Universitiesmentioning
confidence: 99%
See 3 more Smart Citations